Applied biopharmaceutics and pharmacokinetics - Shargel, Leon; Wu-Pong, Susanna;Yu, Andrew B.C (New Jersey : McGraw Hill Education, 2012)
This text integrates basic scientific principles with drug product development and clinical pharmacy practice.
Introduction to Biopharmaceutics and Pharmacokinetics -- Mathematical Fundamentals in Pharmacokinetics -- One-Compartment Open Model: Intravenous Bolus Administration -- Multicompartment Models: Intravenous Bolus Administration -- Intravenous Infusion -- Drug Elimination and Clearance -- Pharmacokinetics of Oral Absorption -- Multiple-Dosage Regimens -- Nonlinear Pharmacokinetics -- Physiologic Drug Distribution and Protein Binding -- Drug Elimination and Hepatic Clearance -- Pharmacogenetics -- Physiologic Factors Related to Drug Absorption -- Biopharmaceutic Considerations in Drug Product Design and In Vitro Drug Product Performance -- Drug Product Performance, In Vivo: Bioavailability and Bioequivalence -- Impact of Drug Product Quality and Biopharmaceutics on Clinical Efficacy -- Modified-Release Drug Products -- Targeted Drug delivery Systems and Biotechnological Products -- Relationship Between Pharmacokinetics and Pharmacodynamics -- Application of Pharmacokinetics to Clinical Situations -- Dose Adjustment in Renal and Hepatic -- Physiologic Pharmacokinetic Models, Mean Residence Time, and Statistical Moment Theory
Includes bibliographical references and index.
Keywords: BIOPHARMACEUTICS -- PHARMACOKINETICS